Ab initio study of the vibrational spectra of amorphous boron nitride - David Hinojosa-Romero; Alexander Valladares; Renela M. Valladares; Isaías Rodríguez; Ariel A. Valladares (Scientific Reports, 2024)
Abstract Boron Nitride (BN) is an interesting polymorphic insulator that is commonly found in four different crystalline structures, each one with different electrical and mechanical properties which makes it an attractive material for technological and industrial applications. Seeking to improve its features, several experimental and simulational works have studied the amorphous phase (a-BN) focusing on electronic and structural properties, pressure-induced phase transformations, and a hydrogenated form of a-BN. By means of ab initio Molecular Dynamics and our well-proven amorphization process known as the undermelt-quench approach, herein three amorphous supercells were computationally generated, two with 216 atoms (densities of 2.04 and 2.80 g cm−3) and a third one with 254 atoms (density of 3.48 g cm−3). The topology, the vibrational density of states and some thermodynamic properties of the three samples are reported and compared with existing experiments and with other computational results.